Utilization of Borrasus flabellifer L. Palm Coir Activated with Potassium Hydroxide (KOH) as an Efficient Adsorbent for Rhodamine B Dye Removal - Matius Stefanus Batu; Maria Magdalena Kolo; Maria Fridolina Taek; Agustina Rosalia Saka (Universitas Pendidikan Mandalika, 2023)
This research paper presents the preparation and characterization of activated charcoal derived from palm coir (Borrassus flabellifer L.) that was activated using potassium hydroxide (KOH). The objective of this study was to assess the key characteristics of the activated charcoal, including moisture content, ash content, and surface area, and to determine the optimal conditions for the adsorption process of Rhodamine B dyes, such as adsorbent mass, contact time, and adsorbate concentration. Additionally, the surface morphology of coir charcoal before and after activation was investigated. The carbonization process was conducted at 300°C for 30 minutes, followed by activation using 1 M KOH for 24 hours. The resulting activated charcoal was subjected to various characterization techniques, including moisture content and ash content analysis, surface morphology examination using scanning electron microscopy (SEM), surface area determination using the Brenauer-Emmet-Teller (BET) method, and functional group identification through Fourier-Transform Infra Red (FTIR) spectroscopy. The findings revealed that the activated charcoal exhibited a water content of 1.537%, an ash content of 16.653%, and a surface area of 36.084 m2/g. The optimal conditions for the adsorption process were determined as follows: 1.0 gram of activated charcoal mass, 30 minutes of contact time, and a rhodamine B concentration of 30 ppm, resulting in adsorption efficiencies of 94.46%, 95.75%, and 94.42%, respectively. Furthermore, the surface morphology analysis demonstrated that non-activated charcoal exhibited irregular particle sizes and small pore sizes, while KOH-activated charcoal displayed an enhanced carbon pore surface and larger pore sizes.